Skyridder, UPM innovation to expedite wire removal on lamp posts - Esam, Asrizam (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
SERDANG – Skyridder, an innovation by Langit Putra Innovative and Creative Group from Putra Science Park (PSP), Universiti Putra Malaysia (UPM), can expedite the usual wire removal work after the advertisement is brought down by 80%.